Altered long non-coding RNA expression profile in rabbit atria with atrial fibrillation: TCONS_00075467 modulates atrial electrical remodeling by sponging miR-328 to regulate CACNA1C. (July 2017) - Li, Zhan; Wang, Ximin; Wang, Weizong; Du, Juanjuan; Wei, Jinqiu; Zhang, Yong; Wang, Jiangrong; Hou, Yinglong
Abstract: Electrical remodeling has been reported to play a major role in the initiation and maintenance of atrial fibrillation (AF). Long non-coding RNAs (lncRNAs) have been increasingly recognized as contributors to the pathology of heart diseases. However, the roles and mechanisms of lncRNAs in electrical remodeling during AF remain unknown. In this study, the lncRNA expression profiles of right atria were investigated in AF and non-AF rabbit models by using RNA sequencing technique and validated using quantitative real-time polymerase chain reaction (qRT-PCR). A total of 99, 843 putative new lncRNAs were identified, in which 1220 differentially expressed transcripts exhibited > 2-fold change. Bioinformatics analysis was conducted to predict the functions and interactions of the aberrantly expressed genes. On the basis of a series of filtering pipelines, one lncRNA, TCONS_00075467, was selected to explore its effects and mechanisms on electrical remodeling. The atrial effective refractory period was shortened in vivo and the L-type calcium current and action potential duration were decreased in vitro by silencing of TCONS_00075467 with lentiviruses. Besides, the expression of miRNA-328 was negatively correlated with TCONS_00075467. We further demonstrated that TCONS_00075467 could sponge miRNA-328 in vitro and in vivo to regulate the downstream protein coding gene CACNA1C. In addition, miRNA-328 could partly reverse the effects of TCONS_00075467 on electrical remodeling. In summary, dysregulated lncRNAs may play important roles in modulating electrical remodeling during AF. Our study may facilitate the mechanism studies of lncRNAs in AF pathogenesis and provide potential therapeutic targets for AF. Highlights: To identify the role of right atrial electrical remodeling in the initiation of AF. The profiles of significantly expressed lncRNAs of right atria in AF and non-AF rabbit models were illustrated. The electrical remodeling related lncRNA was identified through bioinformatics analysis. TCONS_00075467 was demonstrated to have important biological effects on atrial electrical remodeling during AF. TCONS_00075467 could modulate atrial electrical remodeling by sponging miR-328 as a ceRNA to regulate CACNA1C expression.